(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
Pesticide treated seeds may be an important source of food for some birds in times of scarcity and thus a route of pesticide ingestion. The present study was carried out to evaluate the effects of different concentrations of seed dressing pesticide formulations on haematological parameters, egg production and egg quality parameters of Japanese quails. Forty- two adult Japanese quails (Coturnix coturnix japonica) were randomly assigned into 7 groups of six quails each. They were fed diets containing equal amounts of millet seeds treated with dress force and apron at 2.0 g/kg, 2.5 g/kg, and 3.0 g/kg of seed for 8 weeks. Results showed significant (p<0.05) loss in the weight of the birds treated with dress force while weight gain in the apron star-treated quails was significantly lower than the control. The pesticide formulations induced hemotoxicity in the quails dose-dependently including anaemia and leukocytosis. Dress force treated quails recorded significantly lower egg production rate (18.00 ± 4.06 and 17.11 ± 1.04) compared to apron star (40.67 ± 3.23 and 29.00 ± 2.96) at the 2.0 g/kg and 3.0 g/kg doses respectively. Egg weight, shape index, yolk index, and haugh unit of the treated birds were not significantly different from the control birds. The study revealed that the seed dressing formulations were toxic to C. coturnix japonica and affected the growth, hematology and egg production even at recommended doses. Thus, careful attention should be given to their application and use of alternative safe bio-pesticides should be encouraged.